Hubungan Efikasi Diri dan Tingkat Atensi Dengan Activity Daily Living (ADL) Pasien Pasca Stroke - Ni Luh Putu Thrisna Dewi; Ni Ketut Ayu Mirayanti; Ketut Lisnawati; Ni Made Merlin (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2023)
Sudden changes in a person's life after a stroke can cause various negative things in the sufferer, ranging from psychological and behavioral symptoms, including anxiety, feelings of helplessness, mood disorders, low self-efficacy, and impaired attention levels. Psychological problems cause a serious reduction in mobility, because they hinder performance and daily activities or fulfillment of ADLs. This can cause stroke patients to experience job loss and the inability to carry out their social activities. The purpose of this study is the relationship between the self-efficacy of stroke patients and the level of attention to the activity of daily living of post-stroke patients. This study used a correlational analytic method with a Cross-Sectional approach. This research was conducted in one of the private hospitals in Bali, which was held from October 01 - December 30, 2022. With a sample size of 80 respondents of post-stroke patients who control at X Hospital Poly using the Non-probability sampling technique, purposive sampling. The results of this study were that most stroke respondents who experienced low efficacy had a total level of dependence on activity and daily living, as well as stroke who had less attention had a total level of dependence. The results of the correlation test between the two obtained a p-value <0.005 which means there is a significant relationship between efficacy and the level of ADL dependence. This can be an illustration that the psychological condition of post-stroke patients will greatly affect their physical condition. The basis of stroke treatment is of course not only optimizing physical recovery but must also be accompanied by paying attention to the psychological aspects in order to get maximum rehabilitation results.